(untitled) (Current Horticulture, 2024)
The ethnic knowledge on medicinal value of major plants viz. Justicia wynaadensis, Remusatia vivipara, and Bambusa bambos consumed by Kodava tribes in Kodagu District of Karnataka, India was carried out to preserve the herbal/medicinal plant wealth and their proper usage, as there is a decline in human expertise to identify and recognize various medicinal plants. Data were documented using conventional ethnobotanical methods such as interviews and discussion with local populace of Kodava tribals (headmen, healers, and elderly persons) of the study area using a semi-structured questionnaire comprising information about plants and their local names, plant parts used, time of usage, method of sample collection and preparation of dishes, their nutritional and their use in traditional folk medicines, and any other specific comments. The study indicated that J. wynaadensis, locally known as Maddh toppu or Kurinji Toppu or Aati soppu, undergoes a mysterious transformation in terms of chemical constituents during wet and dark months of the monsoon, which is responsible for its medicinal values. During Kakkada padinet, Kodava people consume Maddu Payassa prepared from J. wynaadensis and believe that it generates heat and stabilizes the body temperature, and thus gives resistance against fever and cold during monsoon season. The R. vivipara is known as Mara Kesa, is used in folk medicine to cure inflammation, arthritis, to dispel worms and germs for disinfecting the genito-urinary tract. The consumption of newly emerged bamboo shoots (B .bambos) along with mushrooms is said to balance the body temperatures during heavy rainy days. In summary, the participants of the study underlined that these underutilized vegetables, major components in traditional dishes, offer enhanced nutritional and medicinal values when consumed especially during the monsoon season.